Study of Differences in Blood Sugar Levels of Diabetes Mellitus Patients Who Consume Rice Cooked with the Rice Cooker Method and The Steaming Method - Jamaluddin Jamaluddin; Meutia Zahara; Hermansyah Hermansyah (GLOBAL HEALTH SCIENCE GROUP, 2025)
The 2023 Indonesian Health Survey Report issued by the Ministry of Health revealed that there was an increase in the prevalence of diabetes mellitus (DM) in the population aged over 15 years based on the results of blood sugar level measurements. In the 2018 Basic Health Research, it was recorded that the prevalence of diabetes in Indonesia reached 10.9%. Now, the prevalence has reached 11.7% in 2023. The Aceh Health Office recorded that sufferers of Diabetes Mellitus until early 2023 reached 154,889 cases. The purpose of this study is to find out the difference in blood sugar levels in people with diabetes mellitus who consume rice after cooking with the rice cooker method and with the steaming method. This quantitative analytical research uses a cross-sectional study design. The population of the study was all people with diabetes mellitus at the Calang Health Center, Aceh Jaya Regency, totaling 50 people. Data collection was carried out from January 15 to March 15, 2024 using nonprobability sampling techniques. This study also took direct data by looking at the sugar content of the respondents by eating rice cooked by the rice cooker method and 1 month later by measuring the sugar content of the respondents consuming rice by cooking the rice by steaming. Data were analyzed using univariate, bivariate and multivariate statistical tests. The results of the study showed that factors related to blood sugar levels in DM patients were gender, age, education, occupation, income, physical activity, nutritional status, smoking behavior, and family history of diabetes. The factors most related to increased blood sugar levels in diabetes mellitus patients were steaming with OR=7.47, use of a rice cooker of 11.2 and family history of diabetes mellitus of 7.50. It is expected that respondents will control their blood sugar levels, so that DM sufferers and their families will cook rice using the steaming method, and control other risk factors that can cause high blood sugar levels.